Word stress in English two-syllable words among poesis seminary students - Santa R Sihombing; Selviana Napitupulu (Indonesian Journal Education, 2026)
This study investigates word stress errors in English two-syllable words produced by Poesis Seminary students and examines how these errors affect experiential meaning within Halliday’s experiential metafunction framework. Employing a descriptive qualitative design supported by simple quantitative analysis, the study involved 15 twelfth-grade students selected through purposive sampling. Data were collected through a pronunciation task consisting of ten English two-syllable words and semi-structured interviews. Students’ pronunciations were audio-recorded, transcribed using the International Phonetic Alphabet, and analysed to identify error types, frequency, and meaning distortion. The findings reveal that 65.3% of the pronunciations contained word stress errors, with misplaced stress emerging as the most dominant type. Stress-contrast noun–verb pairs generated more errors than fixed-stress words. Linguistic factors such as Indonesian stress patterns, complex English stress rules, and limited phonological awareness, as well as pedagogical factors including lack of explicit instruction and limited exposure to spoken English, contributed to these errors. From an experiential metafunction perspective, incorrect stress placement frequently altered grammatical roles and distorted intended meaning. The study concludes that word stress should be taught as a meaning-related feature to enhance communicative clarity in EFL contexts.